All these poses, such beautiful Poses: articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright’s direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an “utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo.”1 Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright’s musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the “Clone.” In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.